HYGIENIC ASSESSMENT OF THE STATE OF MINERAL SUPPLY IN THE BODY OF MEDICAL UNIVERSITY STUDENTS - Khaydarov Shovkatjon Madaminjon ugli; Buriboyev Eldar Mamurjonovich; Khakberdiev Khusan Rakhmatulloevich (International Journal of Literature and Language Studies, 2026)
The relevance of the problem. The normal growth, development, metabolism, immune system function, blood formation, stability of the musculoskeletal system, and normal functioning of the nervous system of the human body are directly dependent on an adequate level of mineral substances. Mineral balance is especially important in the bodies of student youth, as during this period the body is influenced by factors such as high mental load, psycho-emotional tension, irregular eating, sleep disorders, and decreased physical activity. Medical university students spend a lot of time on theoretical and practical classes during their studies. Their daily routines are often packed, and their ability to eat regular and balanced meals may be limited. As a result, it is observed that macro- and microelements necessary for the body do not enter the body in sufficient quantities. In particular, a deficiency of elements such as iron, zinc, potassium, magnesium, calcium, and copper can negatively affect students' general health, work capacity, concentration levels, immunity, and academic performance. Iron deficiency leads to anemia, weakness, dizziness, fatigue, and a decrease in mental activity. Zinc deficiency negatively affects the functioning of the immune system, the state of the skin and mucous membranes, cell regeneration, and enzymatic processes. Potassium and magnesium deficiency can cause disorders in the cardiovascular system, neuromuscular conduction, muscle contraction, and general metabolic processes. From this perspective, determining the amount of mineral substances in the bodies of medical university students, comparing them with physiological norms, and assessing existing deficiencies is of great scientific and practical importance.